2014
DOI: 10.16965/ijar.2014.552
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Morphology, Morphometry, Symmetry and Development of External Opening of Carotid Canal With Comparison in Male, Female and Foetus

Abstract: Introduction: The Carotid Canal is an important structure at the base of skull as it conveys the internal carotid artery, along with a sympathetic nerve plexus and a venous plexus. Previous researches done on carotid canal suggest that abnormalities to this canal, such as fractures of carotid canal and carotid sympathetic plexus schwannoma have their effect on the internal carotid artery and the structures passing through it. Cases of absence of carotid canal have also been reported, which causes variations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…According to the results of our study there were no statistically significant differences of the length and width of the EACC between sides and sexes except for the parameter AP which was statistically significant (p = 0.017) between the right and left side on the female skulls. These results are in contrast with those of Aoun et al (2013), and Shaikh & Kulkarni (2014), who found statistically significant differences between male and female skulls in relation to the side. This, the different results of the studies may be related to population differences.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the results of our study there were no statistically significant differences of the length and width of the EACC between sides and sexes except for the parameter AP which was statistically significant (p = 0.017) between the right and left side on the female skulls. These results are in contrast with those of Aoun et al (2013), and Shaikh & Kulkarni (2014), who found statistically significant differences between male and female skulls in relation to the side. This, the different results of the studies may be related to population differences.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were more or less in agreement with previous studies [6][7][8] (Table 3). No literature is available in English to confirm these variations between two sexes.…”
Section: Discussionsupporting
confidence: 94%
“…The probable reason could be the haemodynamic pressure is more in male crania as compared to female crania [9], moreover haemodynamic pressure on right side of the brain, hence diameter of the right CC are more than left side in both sexes. The increased diameter of male CC than female CC is paedomorphic tendency of human skull [8].…”
Section: Discussionmentioning
confidence: 95%
“…We assume that this is caused by the symmetry of the external carotid canal openings in the skulls of both men and women, hence the artery is forced by their position to change its position in relation to the medial line, and thus to the pharyngeal wall. 14 Men presented no asymmetry in any of the abovementioned measurements.…”
Section: Asymmetrymentioning
confidence: 78%